Theory-based assessment in environmental education: a tool for formative evaluation. Issue 2 (7th February 2017) - Granit-Dgani, Dafna; Kaplan, Avi; Flum, Hanoch
Abstract : This article reports on the development of a theory-informed assessment instrument for use in evaluating environmental education programs. The instrument involves coding learners' brief reflective writing on five established educational and social psychological constructs that correspond to five important goals of environmental education: promoting learners' perceived relevance of environmental content, sense of personal and collective responsibility for sustainability, knowledge of environmental content, readiness for environmental action, and identity exploration around environmental questions. The article describes the development of the instrument and its use for coding the reflective writing of 242 early adolescents who participated in a large-scale environmental education program.